OPTIMIZATION OF A FERTILITY RESTORATION METHOD IN OVARIAN RESISTANCE (Global Conference on Medical and Health Sciences, 2026)
Polycystic ovary syndrome (PCOS) is one of the leading causes of endocrine infertility. This study evaluates the effectiveness of conservative, surgical, and combined treatment methods for PCOS. Objective: To evaluate the effectiveness of various fertility restoration methods in patients with PCOS. Material and Methods: This prospective study included 70 women with infertility due to PCOS and 20 women in a control group. Clinical, hormonal, metabolic, and ultrasound parameters were analyzed. Conclusions: A combined approach, including conservative therapy followed by surgical intervention, provides more sustainable restoration of reproductive function.
Keywords: Polycystic ovary syndrome, infertility, fertility, laparoscopy, ovulation stimulation.